Studi Literatur Kandungan Zat Berbahaya pada Skincare dan Dampaknya terhadap Kesehatan Kulit - Eny Widhia Agustin; Mia Hafizah Tumangger; Aisya Nurmaliyah; Naila Syafa Maudy; Cinta Maharanisyah Lubis; Siti Ummu Nur Izzaty; Devika Chandra Kuslinawat; Era Patrika Sakti (An-Najat, 2025)
The use of skin care cosmetics has become an important part of maintaining healthy facial skin. However, there are some cosmetic products that contain hazardous substances such as parabens, mercury, hydroquinone, and retinoic acid that can have harmful effects on skin health, including allergies, irritation, and the risk of cancer. The purpose of this study was to examine the content of hazardous substances in skincare and their impact on skin health. The method used in this study was a literature study. Data were obtained from various secondary sources, including scientific articles, books, and relevant reports. The results of this study based on literature studies showed that there was an average hydroquinone content of 5.432%, an average retinoic acid content of the night whitening cream sample was 0.125%, paraben levels in personal care products, MeP (methylparaben): 77%, PrP (propylparaben): 73%, EtP (ethylparaben): 46%, and BuP (butylparaben): 25%, mercury levels in the SP brand with an average value of 375.525 mg/kg. The use of cosmetics with harmful ingredients can cause skin damage to more serious health problems. Therefore, it is important for consumers to be more vigilant in choosing safe and officially registered cosmetic products.